“E eu não sou palhaça?! dramavivências de palhaças das regiões Norte e Nordeste do Brasil”. - NASCIMENTO, Andressa Passos do (2021)
This research presents questions about gender and notions that make the creations of women clowns viable, allowing us to reflect and discuss the creative paths of the art of clowning made by women, using as a study instrument works by clowns from the North and Northeast regions of Brazil. Using theories such as Regina Horta (1995), Alice Viveiros de Castro (2005), Lélia Gonzalez (1984), Conceição Evaristo (2008) and Ermínia Silva (1996), as well as authors Mário Bolognesi (2003) and Tristan Remy (2016), who helped in the systematization of this study. Therefore, this study proposes to analyze the origins and development of the scene creation process of six clown women. In the context of this investigation an intersection is made between theory and artistic practice, constructing the term "drama experience" to refer to these works, as well as register them, in order to expand the references about clowning done by women, especially those from the North and Northeast regions. This research also highlight the emergence of the gender debate in the study of clowning, as a theoretical instrument that allows an academic and social approach, inserting the figure of the clown as a subject of history.